Magnet Hospitals Perceived by Professional Nurses in Vachira Phuket Hospital - Hnuklub, Orathai; Na takuathung, Usanee (Journal of Health Science of Thailand, 2018)
This cross-sactional research was conducted with the objective of examining the level of magnet hospitals as perceived by professional nurses in Vachira Phuket Hospital The sample group consisted of 176 subjects. The research instrument employed consisted of a set of questionnaire on magnet hospitals according to the perceptions of professional nurses which the researchers created from research instrument of Usanee Na Takuathung (2008). The instrument passed the test with content validity of 0.86. Reliability of the questionnaire was tested and yielded a Cronbachีs alpha coefficient of 0.95. It consisted of the following 4 aspects: administration management, quality of leadership, human resource management and professional practice and service. The statistics used for analyzing the data were percentage, mean and standard deviation. The research findings revealed that the overall perception of magnet hospitals was high ( 3.04, SD 0.50) wherein the aspect with the highest perception was professional practice and service ( 3.36, SD 0.55). The aspect that had the lowest perception was personnel management ( 2.89, SD 0.53) while the topic that had the highest perception was the Nursing Departmentีs policy to have professional nurses provide services for patients in consideration of human compassion ( 3.94, SD 0.97) and the item that had the lowest perception was the perception that nursing administrator had to provide area / room for relax during their shift ( 2.01, SD 0.88).